"They Are Not Like Us" : Understanding Social Exclusion - Lakhani, Sadaf; Sacks, Audrey; Heltberg, Rasmus (World Bank, Washington, DC, 2014)
Negative attitudes toward groups in society are widespread and underpin systematic processes of social exclusion that marginalize people and deny them opportunities and dignity. This paper looks at the processes underlying social exclusion. It uses data covering Eastern Europe and Central Asia to study the responses to a simple hypothetical survey question about which specific groups respondents would not like to have as neighbors. Unwelcoming attitudes toward groups such as immigrants, ethnic minorities, the poor, HIV+ individuals, and others are surprisingly common. These attitudes fall into three distinct clusters: intolerance for the poor and for different lifecycle stages; intolerance toward stigmatized attributes and behaviors; and intolerance toward specific identity groups. An empirical analysis of the determinants of attitudes shows that country-specific factors are far more important than socio-economic characteristics. These findings could have important implications for theories about exclusion and for the design of appropriate social inclusion policies. The authors argue that strategies to address social exclusion need to consider ways to change social norms, attitudes, and behaviors toward disadvantaged groups. The paper explores potential entry points for change within formal and informal institutions.